The extent of audit report lag and governance mechanisms: Evidence from Islamic banking institutions in Malaysia - Kaaroud, Mohamed Ahmed; Mohd. Ariffin, Noraini; Ahmad, Maslina (Emerald Group Publishing, 2020)
The purpose of this study is to examine the extent of audit report lag (ARL) and its association with governance mechanisms in the Islamic banking institutions in Malaysia. The extent of ARL lag is defined by the number of days from a company’s financial year-end to the signature date on its audit report. The sample of the study comprises 112 observations of Islamic banking institutions’ financial reports for the period 2008-2014. A balanced panel data analysis is performed to analyse the association between the extent of ARL and governance mechanisms. The findings show that the extent of ARL for the sample selected ranges from a minimum period of 7 days to a maximum period of 161 days which approximately two months on average. A fixed effects analysis indicates that audit committee expertise and audit committee meeting have significant association with the extent of ARL. On the other hand, board independence, audit committee size and Shari’ah board expertise have insignificant association with the extent of ARL. In addition, one control variable (Islamic bank size) is found to be significantly associated with longer ARL. The findings provide useful feedback for Malaysian policymakers on the past and current practices of financial reports and of governance mechanisms. The findings of the study would help the policymakers in monitoring the Islamic banking institutions’ compliance with financial reports submission requirements. The policymakers perhaps could relook into governance mechanisms that could reduce the extent of ARL in the Islamic banking institutions and implement regulations to strengthen them.